Analysis of Mathematics Problem-solving Ability of Junior High School Students Based on APOS Theory Viewed from the Type of Learning Styles - Rahmah, Kamilia; Inganah, Siti; Darmayanti, Rani; Sugianto, Rahmad; Choirudin, Choirudin; Ningsih, Eka Fitria (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to describe students' mathematical problem-solving based on APOS theory on Kolb's learning styles. This type of research is qualitative with a descriptive approach. The subjects of this study were four students who represented each of Kolb's learning styles. This study's data collection techniques used Kolb's learning styles questionnaire, APOS theory-based problem-solving aptitude test, and unstructured interviews. Data analysis of this research is to reduce data, present data, and draw conclusions. The study results concluded that the subject of assimilator and convergent learning styles could work on problems correctly starting from the action stage, process stage, object stage, and schema stage, although with different problem-solving steps. Subjects with the type of accommodator and diverger learning styles can only solve problems correctly at the action, process, and object stages, while for the schema stage, they have not been able to provide the right solution.